The Impact Behavior between Coal Gangue Particles and the Tail Beam Based on Rock Failure - Zhengyuan Xin; Qingliang Zeng; Yang Yang (Shock and Vibration)
In top coal caving mining, common impact occurs between coal gangue particles and tail beam. Little attention has been paid to the effects of coal gangue particles failure on impact force and tail beam response theoretically, numerically, and experimentally. This paper aims to reveal the influence of coal gangue particles failure on the impact effect of tail beam. First, this paper incorporates the theory of rock failure and energy consumption to assess the impact process of coal gangue particles on the tail beam. A new model to simulate the actual failure conditions of rock particles was developed: the brittle damage-fracture particle model. By comparing damage phenomena and simulation data, the brittle damage-fracture particle model was proved to be correct. Based on this model, a dynamic simulation of brittle coal gangue particles impacting the tail beam was conducted. Then, the dynamic responses of the particles and tail beam were analyzed. The results show that particle failure significantly affects the impact force and dynamic response of the tail beam. The impact effects of coal and gangue particles on the tail beam and their failure energy consumption also differed significantly. This paper stresses the importance of coal gangue particle failure conditions for research on top coal caving mining. Theoretical support is provided for the research of coal gangue identification technology based on the tail beam vibration signal.